The Relationship Between Smoking Habits and Dental and Oral Hygiene in Patients at the Kesamben Community Health Center Dental Clinic in Jombang Regency - Rosita Novayanti Nur Arofah; Bambang Hadi Sugito; Sri Hidayati (International Journal of Advanced Health Science and Technology, 2026)
Smoking remains a major public health concern and is widely recognized as an important behavioral risk factor for poor dental and oral health. Tobacco exposure contributes to plaque accumulation, calculus formation, gingival inflammation, and impaired oral tissue healing. However, evidence regarding the relationship between smoking habits and oral hygiene status in Indonesian primary health care settings is still limited. This study aimed to analyze the association between smoking habits and dental and oral hygiene status among patients attending the Dental Clinic of the Kesamben Community Health Center, Jombang Regency. A quantitative cross-sectional analytical design was employed in March 2025. The study involved 30 male patients aged ≥25 years who were selected using purposive sampling. Smoking habits were assessed using a structured 20-item questionnaire and categorized into low, moderate, and high levels based on cumulative scores. Dental and oral hygiene status was evaluated using the Simplified Oral Hygiene Index (OHI-S), which classifies hygiene conditions into good, moderate, and poor categories. Data were analyzed using univariate and bivariate statistical methods, including the Chi-square test, Spearman correlation analysis, and Phi effect size, with a significance level set at p < 0.05. The results showed that the majority of respondents had high smoking intensity (93.4%) and poor oral hygiene status (96.6%). Statistical analysis revealed a significant association between smoking habits and oral hygiene status (χ² = 7.226; p = 0.007). Spearman correlation analysis indicated a moderate positive relationship between smoking intensity and worsening OHI-S scores (r = 0.52; 95% CI: 0.18–0.74), with a moderate effect size (φ = 0.49). In conclusion, higher smoking intensity is significantly associated with poorer dental and oral hygiene among adult patients at the Kesamben Community Health Center. These findings highlight the importance of integrating smoking cessation counseling with preventive oral health education in primary health care services to improve overall oral health outcomes.